Tashmim Kitab Al-Jaib “Dhiya’ul Muta’allimin” Li Muhadatsah Al-Thullab Fi Al-Ma’had Al-Islamiyah Al-Hasaniyah Ponorogo - Tricahyo, Agus; Mukaromah, Muhimmatul; Wahidah, Zulvata Kholifatul (TSAQOFIYA : Jurnal Pendidikan Bahasa dan Sastra Arab, 2024)
This study aims to determine the design of the Muhadatsah book and the effectiveness of its use at Al-Hasanah Islamic Boarding School. This study uses the Research and Development (R&D) method and data collection using observation, interviews, questionnaires, and tests. The test subjects consisted of material experts, learning design experts, linguists, and 3rd-grade students of Al-Hasanah Islamic boarding school as the target of testing the Arabic conversation product dhiyaul muta'alimin. The results of this study show: 1) The product designed is an Arabic conversation pocket book, "Dhiyaul Muta'alimin", designed to be simple, attractive, and small in size so that it is easy to carry. The material contained in the pocketbook "Dhiyaul Muta'alimin" is the daily conversation material of the santri in the dormitory and is equipped with 'amiya Arabic expressions (the daily language of the Arabs), which will add insight to the santri. 2) Using the pocketbook "Dhiyaul Muta'alimin" in the third grade of Al-Hasanah boarding school is effective. This is shown by the evidence that the results of statistical tests before and after using the "Dhiyaul Muta'alimin" muhadatsah pocketbook increased. Namely the results of the Wilcoxon statistical test in the experimental group given the "Dhiyaul Muta'alimin" pocketbook is the sig value (0.00) < alpha (0.05) so it can be concluded that there is an effect of the "Dhiyaul Muta'alimin" muhadatsah pocket book on student learning outcomes. Abstrak Penelitian ini bertujuan untuk mengetahui perancangan buku Muhadatsah dan efektivitas penggunaannya di Pondok Pesantren Al-Hasanah. Penelitian ini menggunakan metode penelitian Research and Development (R&D) dan pengumpulan data menggunakan observasi, wawancara, angket, dan tes. Subjek uji coba terdiri dari ahli materi, ahli desain pembelajaran, ahli bahasa, dan siswa kelas 3 pondok pesantren Al-Hasanah sebagai sasaran uji coba produk percakapan bahasa Arab dhiyaul muta'alimin. Hasil penelitian ini menunjukkan: 1) Produk yang dirancang adalah Buku saku percakapan bahasa Arab “Dhiyaul Muta’alimin” yang didesain simple, menarik, dan berukuran kecil sehingga mudah untuk dibawa. Materi yang terdapat dalam buku saku “Dhiyaul Muta’alimin” adalah materi percakapan keseharian santri di asrama, dan dilengkapi dengan ungkapan kata bahasa Arab ‘amiyah (bahasa keseharian orang Arab) yang akan menambah wawasan bagi santri. 2) Penggunaan buku saku “Dhiyaul Muta’alimin” di kelas tiga pondok pesantren Al-Hasanah berjalan efektif. Hal ini ditunjukkan dengan bukti bahwa hasil uji statistik antara sebelum dan sesudah menggunakan buku saku muhadatsah “Dhiyaul Muta’alimin” meningkat, yaitu hasil uji statistik wilcoxon pada kelompok eksperimen yang diberikan buku saku “Dhiyaul Muta’alimin” adalah nilai sig (0.00)< alpha (0.05) sehingga bisa disimpulkan bahwa ada pengaruh dari buku saku muhadatsah “Dhiyaul Muta’alimin” pada hasil belajar siswa.